Efficient Passivation of Ag Nanowires with 11‐Mercaptoundecanoic Acid Probed Using In Situ Total‐Internal‐Reflection Surface‐Enhanced Raman Scattering Spectroscopy. Issue 8 (20th February 2019) - Plissonneau, Marie; Madeira, Alexandra; Talaga, David; Bonhommeau, Sébastien; Servant, Laurent; Vallée, Renaud A. L.; Labrugère, Christine; Goldthorpe, Irene A.; Pautrot‐D'Alencon, Lauriane; Le Mercier, Thierry; Treguer‐Delapierre, Mona
Abstract: A promising passivation strategy of one class of Ag nanostructures of high interest for optoelectronics, namely Ag nanowires (AgNWs), with 11‐mercaptoundecanoic acid (MUA) is described. Combining XPS, electron microscopy and original in‐situ total‐internal‐reflection (TIR) surface‐enhanced Raman scattering (SERS) spectroscopic measurements, the substitution of polyvinylpyrrolidone (PVP) molecules on as‐synthesized PVP‐coated AgNWs by their MUA counterparts is clearly demonstrated. The relevance of the SERS approach to examine the anchoring of the MUA onto the silver surface of specific AgNWs with pentagonal cross‐sections is supported by FDTD simulations. In particular, the TIR‐SERS technique reveals that the PVP‐MUA substitution process can be divided into two main steps, namely (i) the desorption of PVP molecules associated with the anchoring of MUA molecules via the formation of Ag−OOC and Ag−S bonds (accomplished within 40 min), and (ii) the subsequent reorientation of MUA molecules to form only Ag−S bonds (finished in 90 min). The resulting passivation of AgNWs with MUA significantly improves their resistance to corrosion, which is crucial for future commercial applications. Abstract : Passivation agent : An efficient passivation of Ag nanowires against corrosion is performed by replacing polyvinylpyrrolidone (PVP) by 11‐mercaptoundecanoic acid (MUA) molecules. An original total‐internal‐reflection surface‐enhanced Raman scattering technique is employed to prove the MUA anchoring on the Ag surface and unravel the PVP‐MUA substitution dynamics.